Assessing market failures in export pioneering activities: A structural estimation approach - WEI, Shang-Jin (Institutional Knowledge at Singapore Management University, 2014)
The paper provides a ﬁrst structural-estimation-based assessment of an influential hypothesis that export pioneers are too few relative to social optimum due to knowledge spillover in new market explorations. Such market failure requires two inequalities to hold simultaneously: the discovery cost is greater than any individual ﬁrm’s expected proﬁt but Smaller than the sum of all potential exporters’ expected proﬁts. Neither has to hold in the data. We estimate the structural parameters based on the customs data of Chinese electronics exports. While we ﬁnd positive discover cost and spillovers, "missing pioneers" are nonetheless a low probability event.